دور الإيرادات النفطية في تمويل الموازنة العامة في ليبيا خلال الفترة (2011–2024م) (Comprehensive Journal of Science, 2026)
This study aims to analyze the role of oil revenues in financing the general budget in Libya during the period (2011–2024), in light of the rentier nature of the Libyan economy and its heavy reliance on oil as the main source of public revenues. The study adopts a descriptive-analytical approach by analyzing data from the Central Bank of Libya.The study reached several findings, most notably the existence of a strong relationship between oil revenues and the state of the general budget (surplus or deficit), as periods of surplus are associated with high oil revenues, while periods of deficit coincide with their decline. The results also showed that the period (2011–2020) was characterized by instability due to political and security disturbances and the closure of oil fields and ports, whereas the period (2021–2024) witnessed a relative improvement in financial performance as a result of increased oil production and improved global oil prices. However, this improvement remained temporary and non-structural in nature.The study concludes that the continued excessive reliance on oil revenues makes public finances vulnerable to fluctuations and external shocks, which calls for the adoption of comprehensive economic, structural, and fiscal reforms aimed at diversifying revenue sources and strengthening the contribution of non-oil sectors in order to achieve economic stability and sustainability.